Calculation of magnetodonor states in InP and polaron effects - Bruno-Alfonso, Alexys [UNESP]; Hai, Guo-Qiang (World Scientific Publishing, 2009)
Far-infrared transitions in polar semiconductors are known to be affected by the presence of shallow donor impurities, external magnetic fields and the electron-LO-phonon interaction. We calculate the magnetodonor states in indium phosphide by a diagonalization procedure, and introduce the electron-phonon interaction by the Fröhlich term. The main effects of this perturbation are calculated by a multi-level version of the Wigner-Brillouin theory. We determine the transition energies, from the ground state to excited states, and find good qualitative agreement with recently reported absorption-spectroscopy measurements in the 100-800 cm-1 range, with applied magnetic fields up to 30 T. Our calculations suggest that experimental peak splittings in the 400-450 cm-1 range are due to the electron-phonon interaction. © 2009 World Scientific Publishing Company.
Keywords: Fröhlich interaction; Magnetodonor; Wigner-Brillouin perturbation theory